Prediction of pathological complete response to neoadjuvant chemotherapy for primary breast cancer comparing interim ultrasound, Shear Wave elastography and MRI - Evans, Andrew; Whelehan, Patsy; Thompson, Alastair; Purdie, Colin; Jordan, Lee; Macaskill, Jane; Waugh, Shelley; Fuller-Pace, Frances; Brauer, Katrin; Vinnicombe, Sarah (Senologie - Zeitschrift für Mammadiagnostik und -therapie, 2018)
Background Prediction of pathological complete response (pCR) of primary breast cancer to neoadjuvant chemotherapy (NACT) may influence planned surgical approaches in the breast and axilla. The aim of this project is to assess the value of interim shear wave elastography (SWE), ultrasound (US) and magnetic resonance imaging (MRI) after 3 cycles in predicting pCR.Methods 64 patients receiving NACT had baseline and interim US, SWE and MRI examinations. The mean lesion stiffness at SWE, US and MRI diameter was measured at both time points. We compared four parameters with pCR status: a) Interim mean stiffness ≤ or > 50 kPat; b) Percentage stiffness reduction; c) Percentage US diameter reduction and d) Interim MRI response using RECIST criteria. The Chi square test was used to assess significance.Results Interim stiffness of ≤ or > 50 kPat gave the best prediction of pCR with pCR seen in 10 of 14 (71 %) cancers with an interim stiffness of ≤ 50 kPat, compared to 7 of 50 (14 %) of cancers with an interim stiffness of > 50 kPat, (p < 0.0001) (sensitivity 59 %, specificity 91 %, PPV 71 %, NPV 86 % and diagnostic accuracy 83 %). Percentage reduction in stiffness was the next best parameter (sensitivity 59 %, specificity 85 %, p < 0.0004) followed by reduction in MRI diameter of > 30 % (sensitivity 50 % and specificity 79 %, p = 0.03) and % reduction in US diameter (sensitivity 47 %, specificity 81 %, p = 0.03). Similar results were obtained from ROC analysis.Conclusion SWE stiffness of breast cancers after 3 cycles of NACT and changes in stiffness from baseline are strongly associated with pCR after 6 cycles.
Keywords: ultrasound; shear wave elastography; breast cancer; neoadjuvant chemotherapy; MR imaging